Peningkatan Kepatuhan Konsumsi Tablet Tambah Darah pada Ibu Hamil melalui Media Edukasi Interaktif di Klinik Sarfina Sembiring Tahun 2025 - Ariska Fauzianty; Friza Novita Sari Situmorang; Sonia Novita Sari; Rismalia Tarigan; Nova Isabella Mariance Br Napitupulu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Anemia in pregnancy remains a public health problem in Indonesia, with a prevalence of 48.9% (Riskesdas, 2018). Low adherence to iron and folic acid tablet (TTD) consumption is one of the main causes of high anemia rates among pregnant women. This community service activity aimed to improve TTD consumption compliance among pregnant women through interactive educational media at Sarfina Sembiring Clinic in 2025. The implementation method applied a participatory learning approach, consisting of preparation, education delivery, evaluation, and follow-up. A total of 30 pregnant women participated in the activity. Pre-test and post-test evaluations showed an increase in knowledge scores from 62.5 to 85.3 (+36.4%), while compliance with TTD consumption increased from 46.7% to 83.3% (+36.6%). Additionally, 90% of participants stated that interactive media was easier to understand compared to conventional lecture methods. These findings indicate that interactive educational media effectively improves knowledge and compliance with TTD consumption among pregnant women, making it a viable alternative for health education to support anemia prevention programs in Indonesia.